First and second law analysis applied to building envelope: A theoretical approach on the potentiality of Bejan's theory - Cesare Biserni; Massimo Garai (Energy Reports, 2015)
Especially in the last decade, efforts have been made in developing the sustainable building assessment tools, which are usually performed based on fundamentals of the First Law of Thermodynamics. However, this approach does not provide a faithful thermodynamic evaluation of the overall energy conversion processes that occur in buildings, and a more robust approach should be followed. The relevance of Second Law analysis has been here highlighted: in addition to the calculation of energy balances, the concept of exergy is used to evaluate the quality of energy sources, resulting in a higher flexibility of strategies to optimize a building design. Reviews of the progress being made with the constructal law show that diverse phenomena can be considered manifestations of the tendency towards optimization captured by the constructal law. The studies based on First and Second Principle of Thermodynamics results to be affected by the extreme generality of the two laws, which is consequent of the fact that in thermodynamics the "any system" is a black box with no information about design, organization and evolution. In this context, an exploratory analysis on the potentiality of constructal theory, that can be considered a law of thermodynamics, has been finally outlined in order to assess the energy performance in building design.
Keywords: 330; Building envelope; Constructal theory; Energy analysis; Exergy and second law balance